Conventional use and sustainable valorization of spent egg-laying hens as functional foods and biomaterials: A review - Hongbing Fan; Jianping Wu (Bioresources and Bioprocessing, 2022)
Abstract Spent hen are egg-laying hens reaching the end of their laying cycles; billions of spent hens are produced globally each year. Differences in people’s attitudes towards spent hen as foods lead to their different fates among countries. While spent hens are consumed as raw or processed meat products in Asian countries such as China, India, Korea, and Thailand, they are treated as a byproduct or waste, not a food product, in the western society; they are instead disposed by burial, incineration, composting (as fertilizers), or rendering into animal feed and pet food, which either create little market value or cause animal welfare and environmental concerns. Despite being a waste, spent hen is a rich source of animal proteins and lipids, which are suitable starting materials for developing valorized products. This review discussed the conventional uses of spent hens, including food, animal feed, pet food, and compost, and the emerging uses, including biomaterials and functional food ingredients. These recent advances enable more sustainable utilization of spent hen, contributing to alternative solutions to its disposal while yielding residual value to the egg industry. Future research will continue to focus on the conversion of spent hen biomass into value-added products. Graphical abstract